The Influence of Environmental Performance, Environmental Cost and ISO 14001 on Financial Performance in Non-Financial Companies Listed on the Indonesia Stock Exchange - Husnah Nur Laela Ermaya; Ayunita Ajengtiyas Saputri Mashuri (Neraca : Jurnal Akuntansi Terapan, 2020)
This study aims to determine the effect of Environmental Performance, Environmental Costs and ISO 14001 on Financial Performance. The independent variable in this study was Environmental Performance measured by using PROPER, Environmental Costs measured by environmental costs incurred by companies, ISO 14001 measured by a dummy with a weight of 1 for companies that have ISO 14001 certification and 0 for and vice versa. The population in this study are all non-financial companies listed on the Indonesia Stock Exchange (IDX) with an observation period of 3 years, 2016- 2018, using a sampling method that is purposive sampling and the total sample obtained is 23 sample companies per year, 2 outlier samples , so that the total sample obtained in this study was 67 samples. The results of this study indicate that environmental performance has a significant positive effect on financial performance, environmental costs have a significant negative effect on financial performance, and ISO 14001 doesn't effect on financial performance.